2018
DOI: 10.3390/dj6020012
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: The Use of Tooth Particles as a Biomaterial in Post-Extraction Sockets. Experimental Study in Dogs

Abstract: Objectives: The objective of this study was to evaluate new bone formation derived from freshly crushed extracted teeth, grafted immediately in post-extraction sites in an animal model, compared with sites without graft filling, evaluated at 30 and 90 days. Material and Methods: The bilateral premolars P2, P3, P4 and the first mandibular molar were extracted atraumatically from six Beagle dogs. The clean, dry teeth were ground immediately using the Smart Dentin Grinder. The tooth particles obtained were subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…Calvo-Guirado et al, in a study on beagle dogs, hystologically demonstrated the formation of new well-organized bone, with multiple osteons at 90 days after dentin autograft. Hystomorphometry revealed the presence of higher percentages of mature bone and less percentages of immature bone in the sites grafted with particulated dentin when compared with no-grafted sites at 90 days [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calvo-Guirado et al, in a study on beagle dogs, hystologically demonstrated the formation of new well-organized bone, with multiple osteons at 90 days after dentin autograft. Hystomorphometry revealed the presence of higher percentages of mature bone and less percentages of immature bone in the sites grafted with particulated dentin when compared with no-grafted sites at 90 days [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after the extraction ( Figure 1 ), the right molar's fragments were grinded for 3 seconds (300-1200 μ m) by the use of the Smart Dentin Grinder™ (KometaBio, Fort Lee, NJ, USA) and then immersed into a 0.5 M NaOH and 20% ethanol solution for 10 minutes, in order to dissolve all the organic remains from the tubules. The particulate was first dried with a sterile gauze, then rinsed two times (3 minutes each) with phosphate-buffered saline solution to remove all the NaOH and the ethanol [ 16 , 23 ]. The right postextractive socket (test site) was filled with the grinded dentin; then, the left one (control site) was filled with a fibrin sponge.…”
Section: Case Presentationmentioning
confidence: 99%
“…We have been made aware that Figure 7d of paper [ 1 ] is similar to Figure 11a of a paper published in Applied Sciences [ 2 ]. Both figures show histological images from dogs for experiments carried out in different research projects.…”
mentioning
confidence: 99%
“…The authors were unable to provide an adequate explanation for the similarity. The Editor-in-Chief and the Editorial Office have therefore taken the decision to retract the paper [ 1 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation